Simulation study of biomechanical properties of porous titanium alloy spinal cage using ct-fea - Muhammad Shahruddin, Azmi (2024)
Interbody fusion devices, like spinal cages, are pivotal in stabilizing the spine and mitigating symptoms related to degenerative disc disease (DDD), which stems from factors like ageing, obesity, smoking, trauma, poor body mechanics, spinal instability, and inflammatory conditions. However, subsidence usually occurs clinically due to changes in the Elastic Modulus between the spinal cage and the vertebral bones. Therefore, the porous structure may reduce the elastic modulus of the lumbar cage. This study aims to develop and evaluate the porosity of spinal cages made of titanium alloy with inhomogeneous L4-L5 Lumbar spines to enhance the integration of mechanical features with bone and avoid stress shielding for bone tissue engineering applications. The Finite Element Analysis (FEA) was used to analyse two pattern designs, each with eight specimens of different porosity of the spinal cage assembly between the L4-L5 vertebral bones. Meanwhile, Specimen 0 acted as a control for this study. Specimens 1 to 5 have a hole porosity design, while specimens 6 to 7 have a slot porosity design. The file from Computed Tomography (CT) scans of the lumbar L4-L5 were performed to generate accurate 3D models. The material properties of the lumbar L4-L5 were modified by creating an inhomogeneous material model based on the 3D model of the lumbar, which was then utilised in the FEA to examine the stress behaviour of the titanium alloy interbody cage and determine the L4-L5 stress distribution with the cage. The results showed that specimen 5 has the greatest porosity value of the cages, 58.76% for pattern one and 34.9% for pattern two. The results showed that specimen 5 displayed the lowest maximum stress and total deformation in both designs, making it more stable and durable. The von Mises stress value of the cages is 719 MPa for pattern one and 151 MPa for pattern two. As a result, it was confirmed that the 3D model is inhomogeneous and reliable for FEA analysis. The biomechanical behaviour of the post-implant cage has been estimated using a mathematical model developed using simulation and test data. Recommendations for future research are needed to perform experimental testing of the spinal cage assemblies in the lab to validate the results and ensure the cages are safe and effective.